Development Of Indonesia Submarine Force Structure Based On Analytical Hierarchy Process (AHP) And Interpretive Structural Modeling (ISM) To Control National Interest At Sea - Mei Edi Prayitno; Yanuar Yanuar (International Journal of Marine Engineering Innovation and Research, 2020)
As a maritime country, Indonesia is rich in natural resources, resulting in theft and territorial violations, so it needs to increase sea power, including submarines. Currently, Indonesia is developing submarines, so it is necessary to choose the best alternatives and elements to control national interests at sea. The research objectives are to find out the best alternative, the key element in developing submarine force structure, and the implications for national interests at sea. The research method is carried out by conducting a literature study to compile a questionnaire and consulting with experts to determine the best variables and sub-elements and followed by a survey of participants as a purposive random sampling using the analytical hierarchy process and interpretive structural modeling. From the research results, the five highest alternative variables are vision and mission (0.102), shipyard (0.90), government policy (0.84), technology transfer (0.56), and budget (0.53). Whereas the key sub-elements of development of submarine force structure are improving the quality of education, the need for the government's political will, national interests, national defense policy, and the role of the defense ministry. By increasing the submarine force structure will be able to maintain the national interest in the sea in protecting natural resources and prevent territorial violations.